The Prevalens of Ototoxicity in Drug Resistance Tuberculosis Patients and The Associated Factors at Persahabatan General Central Hospital - Ismulat Rahmawati; Fathiyah Isbaniah; Heidy Agustin; Raden Ena Sarikencana (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: The treatment of drug resistance tuberculosis needs second line injection antituberculosis drug that associated with irreversible ototoxic. The aim of this study is to know the prevalence of ototoxicity in tuberculosis drug resistance patients and the contributing factors. Methods: This is a cross sectional study among drug resistance TB patients who receive kanamysin or capreomycin as a part of drug regimen during intensive phase in January to September 2017 at Persahabatan hospital. Ototoxic defined according to American Speech Language and Hearing Association (ASHA) 1994 criteria by comparing baseline audiometric examination before treatment with current result. Results: Seventy-two patients were included in this study. The prevalence of ototoxicity was found in 34 patients (47,2%). Ototoxic found in 5 subjects (14,7%) during the first month of treatment and 19 subjects (56%) without hearing disturbance complain. Ototoxic in kanamisin group (47,9%) is more frequent compared with capreomisin (36,8%). Ototoxicity was associated with age, the risk increases 5% every 1 year older p=0,029 aOR:1,050 IK95% (1,005-1,096). The prevalences of ototoxicity are higher in diabetes and increasing serum creatinin patients but statistically not significance. Sex, body mass index, the history of using injectable antiTB drug, HIV status and total dosis were not associated with ototoxicity. Conclusion: Ototoxicity is common in intensive phase of drug resistance tuberculosis treatment. Further study needed to determine the association of contributing factors. (J Respir Indo. 2019; 39(3):180-95)